Pengaruh model talking stick cerita rakyat terhadap kemampuan berbicara peserta didik kelas V di sekolah dasar - Handayani Pamungkas; Septi Yulisetiani (Didaktika Dwija Indria, 2025)
This study aims to analyze the effect of using the talking stick model in improving the speaking ability of grade V students through retelling folktales. The talking stick model, which is based on active and interactive participation, is designed to overcome students obstacles in speaking, such as nervousness and lack of confidence, while instilling local cultural values. The research method used pretest and posttest to measure the improvement of speaking ability, with assessment instruments of linguistic, non-language aspects, and story content. The results showed that the application of the talking stick model significantly improved students speaking ability, supported by statistical tests that showed a significance value of 0.001. In addition to improving language competence, the application of this model is also able to strengthen social and cultural aspects and build students confidence. The findings recommend the use of the talking stick model as a fun and effective learning alternative in an effort to improve speaking skills as well as cultural preservation through folklore.